Tingkat Keterampilan Teknik Dasar Servis dalam Ketepatan Akurasi pada Pembelajaran Bulutangkis Siswa Kelas 8 SMPN 5 Karawang Barat - Nasution, Nana Suryana; Fauzi, Dira; Burhan, Acep (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
ABSTRACT This writing aims to find out how well badminton players can perform short serves and long serves as measured by the correlation coefficient. This writing is quantitative and uses survey methodology, with measurements and tests used for data collection. The population of this study was all students at levels VIII A to VIII K, with a total of 390 students, and sampling used cluster random sampling with a total of 20 people. From the written findings, seven students can hit accurate short serves with a good category score of 35%, and seven students have a score of 35% or more, seven students have a score of 35% or less, and six students. Have a score of less than 30%. Long Serve Skills were obtained by 25% in the excellent category from 5 students, 45% in the adequate category from 9 students, and 30% in the unsatisfactory category from 6 students. Conclusion: It is significantly influenced by several elements, such as poorly planned practice, inappropriate methods, and unreasonable practice expectations from students. Short and long serves accuracy increases with better hitting technique, especially when testing. Keywords: Badminton, short serve, and long serve